Duty as a defence between civil disobedience and criminal law: Peer reviewed article (Italian Review of Legal History, 2021)
The history of civil disobedience begins in the United States in the 17th century and has evolved during the centuries. The most modern type of civil disobedience, whistleblowing, is emblematic of how the concept has changed over the last decades.The question of which circumstances justify disobedience to the law is one of the most debated in the history of legal thought. The article analyses the relationship between morality and criminal law or, in other words, between the right (and duty) to disobey certain laws and its consequences.
Keywords: Civil disobedience; whistleblowing; criminal law; legal duty; moral duty